Preparation method and application of aramid fiber core layer surface co-assembly array sheath structure composite material
By preparing the aramid fiber core layer surface co-assembled array sheath structure composite material, the problems of low energy density and mechanical properties and capacitance imbalance of fibrous supercapacitors are solved, and high energy density and excellent mechanical properties and capacitance balance are achieved.
Patent Information
- Application Number
- CN202510253185.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
Existing fiber-like supercapacitors assembled with existing fibers have low energy density and cannot achieve a balance between mechanical properties and capacitance.
The preparation method of co-assembled array sheath structure composite material on the surface of the aramid fiber core layer was used to prepare the MXene solution by adding titanium aluminum carbide to lithium fluoride/hydrochloric acid solution, and adding metal molybdenum and ethanol solution to the hydrogen peroxide solution to prepare the MoO3 nanodispersion solution. Then, the aramid nanofiber gel containing magnesium ions was immersed into the MoO3/MXene blend solution. After drying, the MoO3/MXene was distributed perpendicularly along the central axis of the aramid nanofiber.
It has achieved high energy density and excellent mechanical properties and capacitance balance, with tensile strength of 60~100MPa, conductivity of 1000~2000S/cm, volume specific capacitance of 1300~2700F/cm3, and capacitance retention rate of 75~98%.
Smart Images

Figure CN119742189A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible composite materials, and more specifically, to a preparation method and application of a composite material having an aramid fiber core layer surface co-assembled array sheath structure. Background Art
[0002] With the rapid development of human-machine interface (HMI) technology and the Internet of Things (IoT), flexible wearable smart devices with multifunctionality and user-friendly characteristics, such as wearable energy storage devices, bioelectronic devices, and stress-strain sensors, are increasingly attracting widespread attention. At present, a variety of materials such as fibers, films, and aerogels have been applied to the design of wearable smart devices. Among them, multifunctional smart fibers have shown unique importance due to their lightweight, good flexibility, multi-scale design capabilities, and advantages in integration with large-scale textile systems. At present, a variety of functional fibers with excellent mechanical and electrochemical properties have been developed, including carbon-based fiber electrodes, pseudocapacitive nanocomposite fibers, and conductive polymer fibers. Using these functional fiber electrodes, the corresponding fiber-shaped supercapacitors (FSCs) were successfully assembled.
[0003] However, the energy density of the fiber-shaped supercapacitor assembled according to the above fibers is low, and when the above fibers are required to meet mechanical properties (such as high flexibility and strength), their capacitance performance will be affected, that is, it is impossible to achieve a balance between mechanical properties and capacitance. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer, which is used to solve the technical problems that the energy density of existing fiber-assembled fiber-shaped supercapacitors is low and the balance between mechanical properties and capacitance cannot be achieved. In view of this, the present invention is implemented through the following scheme.
[0005] In a first aspect, the present invention provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: Titanium aluminum carbide is added to a lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained; Add metal molybdenum and ethanol solution to hydrogen peroxide solution and perform hydrothermal treatment for 6 to 12 hours to obtain MoO3 nano-dispersion with oxygen vacancies; wherein the temperature of the hydrothermal treatment is 140 to 180°C, and the concentration of the ethanol solution is 20 to 50 Vol%; Obtaining a MoO3 / MXene blended solution according to the MXene solution and the MoO3 nanodispersion; The aramid nanofiber gel containing magnesium ions is impregnated into the MoO3 / MXene blend solution, and after drying, an ANFs@MoO3 / MXene composite material is obtained.
[0006] Compared with the prior art, the ANFs@MoO3 / MXene composite material prepared by the method for preparing a composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer of the present invention has an aramid nanofiber (ANFs) as a core layer, a co-assembled array sheath structure of MoO3 / MXene, and the co-assembled array sheath structure surrounds the aramid nanofiber (ANFs) and is vertically distributed along the central axis of the aramid nanofiber, so that the composite material has high energy density, and excellent mechanical properties and capacitance balance characteristics; specifically, the present invention selects reasonable reagents or raw materials, and controls the conditions of each step within the above reasonable range, firstly utilizes titanium A MXene solution is prepared by using aluminum carbide and lithium fluoride / hydrochloric acid solution, and then a MoO3 nano-dispersion liquid with oxygen vacancies is prepared by using metal molybdenum, hydrogen peroxide solution and ethanol solution, thereby obtaining a MoO3 / MXene blend solution; further, the present invention introduces magnesium ions into the aramid nanofiber gel, and the magnesium ions are uniformly distributed inside and / or on the surface of the aramid nanofiber gel, and the MoO3 / MXene blend solution is assembled onto the outer surface of the aramid nanofiber (ANFs) through the electrostatic adsorption of the magnesium ions (i.e., positive ions), and after drying, the MoO3 / MXene is vertically distributed along the central axis of the aramid nanofiber (see Figure 1 ), the special structure of the ANFs@MoO3 / MXene composite material determines that the material has the above-mentioned excellent properties. Specifically, in the embodiment of the present invention, after the above-mentioned ANFs@MoO3 / MXene composite material is prepared, the performance test is carried out on it. The tensile strength of the ANFs@MoO3 / MXene composite material is 60~100MPa, the conductivity is 1000~2000S / cm, and the current density is 3mA / cm 3 When the volume specific capacitance is 1300~2700F / cm 3 , at a current density of 5A / g, the capacitance retention rate is 75-98% after 10,000 charge-discharge cycles. The above technical solution of the present invention solves the technical problems that the energy density of the existing fiber-assembled fiber-shaped supercapacitor is low and the balance between mechanical properties and capacitance cannot be achieved.
[0007] Furthermore, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, in the lithium fluoride / hydrochloric acid solution, the concentration of hydrochloric acid is 9-12 mol / L; the volume of hydrochloric acid required for every 4-8 grams of lithium fluoride is 30-120 mL; and / or, The mass ratio of the titanium aluminum carbide to the lithium fluoride is 1:(1.6-2).
[0008] Furthermore, in the preparation method of the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, titanium aluminum carbide is added to a lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained, comprising: Adding the titanium aluminum carbide to the lithium fluoride / hydrochloric acid solution, and stirring for 20 to 50 hours at a temperature of 25 to 50° C. to obtain a first solution; the stirring rate is 100 to 150 rpm; The first solution is centrifuged, washed to neutrality, and subjected to ultrasonic treatment for 1 to 2 hours to obtain a second solution; the centrifugal speed is 3000 to 4000 rpm, and the ultrasonic treatment power is 100 to 250 W; After the second solution is centrifuged again, a supernatant is obtained; the supernatant is the MXene solution; wherein the re-centrifugation rate is 1000~4000rpm, and the centrifugation time is 0.5~2 hours.
[0009] Furthermore, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, in the process of adding metal molybdenum and ethanol solution to the hydrogen peroxide solution, the mass of metal molybdenum required for every 12-20 mL of the hydrogen peroxide solution is 0.5-2 grams; and / or, The volume ratio of the ethanol solution to the hydrogen peroxide solution is 1:(0.5~1).
[0010] Furthermore, in the preparation method of the aramid fiber core layer surface co-assembled array sheath structure composite material of the present invention, in the MoO3 / MXene blended solution, the volume ratio of the MXene solution to the MoO3 nano-dispersion is 1: (0.05~0.15).
[0011] Furthermore, in the preparation method of the aramid fiber core layer surface co-assembled array sheath structure composite material of the present invention, in the process of impregnating the aramid nanofiber gel containing magnesium ions into the MoO3 / MXene blended solution, the mass ratio of the aramid nanofiber gel containing magnesium ions to the MoO3 / MXene blended solution is 1: (100~150).
[0012] Furthermore, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, the magnesium ion content in the aramid nanofiber gel containing magnesium ions is 5-10wt%; and / or, The method for obtaining the aramid nanofiber gel containing magnesium ions comprises: The para-aramid fiber is dissolved to prepare a 10-20 mg / mL aramid nanofiber spinning solution; The aramid nanofiber spinning solution is subjected to spinning treatment to obtain an aramid nanofiber gel after coagulation; the injection speed of the spinning treatment is 500-1000 μL / min, and the coagulation bath is deionized water; The aramid nanofiber gel is immersed in a 1-10 wt % magnesium chloride hexahydrate solution and mixed evenly to obtain the aramid nanofiber gel containing magnesium ions.
[0013] Furthermore, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, the drying process is carried out in a vacuum environment; The vacuum degree of the vacuum environment is 0.01-0.09 MPa, the drying temperature is 35-80° C., and the drying time is 0.5-6 hours.
[0014] In the second aspect, the present invention provides a composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer, which is prepared according to the preparation method of the composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer; wherein the core layer of the composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer is an aramid nanofiber, and the co-assembled array sheath structure is MoO3 / MXene; the co-assembled array sheath structure surrounds the aramid nanofiber and is vertically distributed along the central axis of the aramid nanofiber.
[0015] Compared with the prior art, the beneficial effects of the aramid fiber core layer surface co-assembled array sheath structure composite material of the present invention are the same as the beneficial effects of the preparation method of the aramid fiber core layer surface co-assembled array sheath structure composite material described in the above technical scheme, and will not be repeated here.
[0016] In a third aspect, the present invention provides the use of the above-mentioned aramid fiber core layer surface co-assembled array sheath structure composite material as an electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a partially enlarged schematic diagram of the sheath cross-sectional structure of the ANFs@MoO3 / MXene composite material prepared in Example 1; Figure 2 Schematic diagram of the planar structure of the ANFs@MoO3 / MXene composite material prepared in Example 1; Figure 3This is a schematic diagram of the cross-sectional structure of the ANFs@MoO3 / MXene composite material prepared in Example 1; Figure 4 XRD spectrum of the core layer ANFs of the ANFs@MoO3 / MXene composite material prepared in Example 1; Figure 5 This is the XRD spectrum of the sheath layer of the ANFs@MoO3 / MXene composite material prepared in Example 1; Figure 6 Schematic diagram of the mechanical properties of the ANFs@MoO3 / MXene composite material prepared in an embodiment of the present invention; Figure 7 CV schematic diagram of the ANFs@MoO3 / MXene composite material prepared in an embodiment of the present invention as an electrode; Figure 8 This is a schematic diagram of the volume capacity comparison of the ANFs@MoO3 / MXene composite material prepared in an embodiment of the present invention; Fig. 9 Schematic diagram of the cyclic stability of the ANFs@MoO3 / MXene composite material prepared in an embodiment of the present invention when used as an electrode. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0019] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.
[0021] At present, a variety of materials such as fibers, films, and aerogels have been applied to the design of wearable smart devices. Among them, multifunctional smart fibers have shown unique importance due to their lightweight, good flexibility, multi-scale design capabilities, and advantages of integration with large-scale textile systems. At present, a variety of functional fibers with excellent mechanical and electrochemical properties have been developed, including carbon-based fiber electrodes, pseudocapacitive nanocomposite fibers, and conductive polymer fibers. Using these functional fiber electrodes, the corresponding fibrous supercapacitors (FSCs) were successfully assembled. However, the energy density of the fibrous supercapacitors assembled from the above fibers is low, and when the mechanical properties of the above fibers (such as high flexibility and strength) are met, their capacitance performance will be affected, that is, the balance between mechanical properties and capacitance cannot be achieved.
[0022] In order to solve the above technical problems, in a first aspect, the present invention provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: Titanium aluminum carbide is added to a lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained; Add metal molybdenum and ethanol solution to hydrogen peroxide solution and perform hydrothermal treatment for 6 to 12 hours to obtain MoO3 nano-dispersion with oxygen vacancies; wherein the temperature of the hydrothermal treatment is 140 to 180°C, and the concentration of the ethanol solution is 20 to 50 Vol%; Obtaining a MoO3 / MXene blended solution according to the MXene solution and the MoO3 nanodispersion; The aramid nanofiber gel containing magnesium ions is impregnated into the MoO3 / MXene blend solution, and after drying, an ANFs@MoO3 / MXene composite material is obtained.
[0023] In the case of adopting the above technical scheme, the ANFs@MoO3 / MXene composite material prepared by the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention has aramid nanofibers (ANFs) as the core layer, and the co-assembled array sheath structure is MoO3 / MXene. The co-assembled array sheath structure surrounds the aramid nanofibers (ANFs) and is vertically distributed along the central axis of the aramid nanofibers, so that the composite material has high energy density, and excellent mechanical properties and capacitance balance characteristics; specifically, the present invention selects reasonable reagents or raw materials, and controls the conditions of each step within the above reasonable range, first A MXene solution is prepared by using titanium aluminum carbide and lithium fluoride / hydrochloric acid solution, and then a MoO3 nano-dispersion liquid with oxygen vacancies is prepared by using metal molybdenum, hydrogen peroxide solution and ethanol solution, thereby obtaining a MoO3 / MXene blended solution; further, the present invention introduces magnesium ions into the aramid nanofiber gel, and the magnesium ions are uniformly distributed inside and / or on the surface of the aramid nanofiber gel, and the MoO3 / MXene blended solution is assembled onto the outer surface of aramid nanofibers (ANFs) through the adsorption of the magnesium ions (i.e., positive ions), and after drying, the MoO3 / MXene is vertically distributed along the central axis of the aramid nanofiber (see Figure 1 ), the special structure of the ANFs@MoO3 / MXene composite material determines that the material has the above-mentioned excellent properties. Specifically, in the embodiment of the present invention, after the above-mentioned ANFs@MoO3 / MXene composite material is prepared, the performance test is carried out on it. The tensile strength of the ANFs@MoO3 / MXene composite material is 60~100MPa, the conductivity is 1000~2000S / cm, and the current density is 3mA / cm 3 When the volume specific capacitance is 1300~2700F / cm 3 , at a current density of 5A / g, the charge and discharge cycle is 10,000 times, and the capacitance retention rate is 75-98%. Through the above technical solution of the present invention, the technical problem that the energy density of the existing fiber-assembled fiber-shaped supercapacitor is low and the balance between mechanical properties and capacitance cannot be achieved is solved; for example, in the above technical solution, the time of the hydrothermal treatment can be 6 hours, 8 hours, 10 hours or 12 hours, the temperature of the hydrothermal treatment can be 140°C, 160°C or 180°C, and the concentration of the ethanol solution can be 20Vol%, 35Vol% or 50Vol%.
[0024] It should be understood that in the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention, in order to obtain an array sheath structure with excellent performance, that is, in order to obtain a MXene with excellent performance, the concentration of hydrochloric acid should also be controlled, and the amount of lithium fluoride, hydrochloric acid and titanium aluminum carbide should be within a reasonable range; for example, the concentration of the hydrochloric acid can be 9~12mol / L, the volume of hydrochloric acid required for every 4~8 grams of lithium fluoride can be 30~120mL, and the mass ratio of the titanium aluminum carbide to the lithium fluoride can be 1:(1.6~2); for another example, the concentration of the hydrochloric acid can be 9mol / L, 11mol / L or 12mol / L, the volume of hydrochloric acid required for every 4g, 6g or 8g of lithium fluoride can be 30mL, 60mL, 90mL or 120mL, and the mass ratio of the titanium aluminum carbide to the lithium fluoride can be 1:1.6, 1:1.8 or 1:2.
[0025] As a possible implementation mode, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, titanium aluminum carbide is added to a lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained, comprising: Step 1, adding the titanium aluminum carbide to the lithium fluoride / hydrochloric acid solution, and stirring for 20 to 50 hours at a temperature of 25 to 50° C. to obtain a first solution; the stirring rate is 100 to 150 rpm; Step 2, centrifuging the first solution, washing it to neutrality, and ultrasonically treating it for 1 to 2 hours to obtain a second solution; the centrifugal speed is 3000 to 4000 rpm, and the power of the ultrasonic treatment is 100 to 250 W; Step 3, after the second solution is centrifuged again, a supernatant is obtained; the supernatant is the MXene solution; wherein the re-centrifugation rate is 1000~4000rpm, and the centrifugation time is 0.5~2 hours.
[0026] In the case of adopting the above technical scheme, in the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention, by controlling the temperature, stirring time and stirring rate in the above reasonable range in step 1, it is conducive to stably and controllably carrying out the reaction of titanium aluminum carbide and lithium fluoride / hydrochloric acid; further, in step 2, by centrifugation and washing to neutrality, unreacted titanium aluminum carbide and other impurities can be removed, thereby improving the purity of the MXene solution, and the MXene flakes can be further dispersed by water bath ultrasonic treatment to prevent them from agglomerating, thereby improving the uniformity and stability of the MXene solution; further, in step 3, by centrifugation again, the suspended matter and impurities in the solution can be further removed to obtain a MXene solution with fewer flakes. liquid; the MXene solution obtained by the present technical scheme is black; for example, in the above technical scheme, the temperature of step 1 can be 25°C, 35°C or 50°C, the stirring time can be 20 hours, 35 hours or 50 hours, and the stirring rate can be 100rpm, 130rpm or 150rpm; the ultrasonic treatment time of step 2 can be 1 hour, 1.5 hours or 2 hours, the centrifugal rate can be 3000rpm, 3500rpm or 4000rpm, and the power of the ultrasonic treatment can be 100W, 180W or 250W; the re-centrifugation rate of step 3 can be 1000rpm, 2500rpm or 4000rpm, and the centrifugal time can be 0.5 hour, 1.5 hours or 2 hours.
[0027] It should be understood that in the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention, in order to obtain an array sheath structure with excellent performance, that is, in order to obtain a MoO3 nano-dispersion with excellent performance, the concentration of the hydrogen peroxide solution should also be controlled, and the amount of the hydrogen peroxide solution, the metal molybdenum and the ethanol solution should be within a reasonable range; for example, the concentration of the hydrogen peroxide solution can be 5~15wt%, the mass of the metal molybdenum required for every 12~20mL of the hydrogen peroxide solution can be 0.5~2 grams, and the volume ratio of the ethanol solution to the hydrogen peroxide solution can be 1:(0.5~1); for another example, the concentration of the hydrogen peroxide solution can be 5wt%, 8wt% or 15wt%, the mass of the metal molybdenum required for every 12mL, 16mL or 20mL of the hydrogen peroxide solution can be 0.5 grams, 1.3 grams or 2 grams, and the volume ratio of the ethanol solution to the hydrogen peroxide solution can be 1:0.5, 1:0.8 or 1:1.
[0028] As described above, the co-assembled array sheath structure of the ANFs@MoO3 / MXene composite material prepared by the above technical solution of the present invention is MoO3 / MXene. How to stably assemble the co-assembled array sheath structure onto the surface of the core aramid nanofiber (ANFs) and make the co-assembled array sheath structure vertically distributed along the central axis of the aramid nanofiber? On the one hand, the present invention introduces magnesium ions into the aramid nanofiber gel. On the other hand, the present invention also needs to control the mixing ratio of the MXene solution and the MoO3 nanodispersion, and the aramid nanofiber gel containing magnesium ions and the MoO3 / MXene blend solution within a reasonable range; for example, in the MoO3 / MXene blend solution, The volume ratio of the MXene solution to the MoO3 nano-dispersion can be 1:(0.05~0.15), and in the process of impregnating the aramid nanofiber gel containing magnesium ions into the MoO3 / MXene blended solution, the mass ratio of the aramid nanofiber gel containing magnesium ions to the MoO3 / MXene blended solution can be 1:(100~150); as another example, the volume ratio of the MXene solution to the MoO3 nano-dispersion can be 1:0.05, 1:0.1 or 1:0.15, and the mass ratio of the aramid nanofiber gel containing magnesium ions to the MoO3 / MXene blended solution can be 1:100, 1:130 or 1:150.
[0029] As a possible implementation manner, in the method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure of the present invention, the magnesium ion content in the aramid nanofiber gel containing magnesium ions is 5-10wt%; and / or, The method for obtaining the aramid nanofiber gel containing magnesium ions comprises: Step 1, dissolving the para-aramid fiber to prepare a 10-20 mg / mL aramid nanofiber spinning solution; Step 2, spinning the aramid nanofiber spinning solution to obtain an aramid nanofiber gel after coagulation; the injection speed of the spinning treatment is 500-1000 μL / min, and the coagulation bath is deionized water; Step 3: immersing the aramid nanofiber gel in a 1-10 wt % magnesium chloride hexahydrate solution and mixing the mixture evenly to obtain an aramid nanofiber gel containing magnesium ions.
[0030] When the above-mentioned technical scheme is adopted, in the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention, the aramid fiber is made into an aramid nanofiber spinning solution, which is then spun, and the solidified aramid nanofiber gel is immersed in a 1~10wt% magnesium chloride hexahydrate solution, thereby obtaining an aramid nanofiber gel containing magnesium ions; in the above-mentioned technical scheme, for example, the magnesium ion content in the aramid nanofiber gel containing magnesium ions is 5wt%, 8wt% or 10wt%, the concentration of the aramid nanofiber spinning solution can be 10mg / mL, 15mg / mL or 20mg / mL, the injection speed of the spinning treatment can be 500μL / min, 800μL / min or 1000μL / min, and the concentration of the magnesium chloride hexahydrate solution can be 1wt%, 5wt% or 10wt%.
[0031] It should also be understood that in the preparation method of the aramid fiber core layer surface co-assembled array sheath structure composite material of the present invention, in order to avoid oxidation of the composite material during the drying process so that the prepared composite material has better performance, the present invention controls the above-mentioned drying process to be carried out in a vacuum environment; by way of example, the vacuum degree of the vacuum environment can be 0.01~0.09MPa, the drying temperature can be 35~80℃, and the drying time can be 0.5~6 hours; by way of another example, the vacuum degree of the vacuum environment can be 0.01Mpa, 0.05Mpa or 0.09Mpa, the drying temperature can be 35℃, 55℃ or 80℃, and the drying time can be 0.5 hours, 3 hours or 6 hours.
[0032] In the second aspect, the present invention provides a composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer, which is prepared according to the preparation method of the composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer; wherein the core layer of the composite material of a co-assembled array sheath structure on the surface of an aramid fiber core layer is an aramid nanofiber, and the co-assembled array sheath structure is MoO3 / MXene; the co-assembled array sheath structure surrounds the aramid nanofiber and is vertically distributed along the central axis of the aramid nanofiber.
[0033] In the case of adopting the above technical scheme, the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer of the present invention is prepared by the preparation method of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer. The ANFs@MoO3 / MXene composite material has aramid nanofibers (ANFs) as the core layer, and the co-assembled array sheath structure is MoO3 / MXene. The co-assembled array sheath structure surrounds the aramid nanofibers (ANFs) and is vertically distributed along the central axis of the aramid nanofibers, so that the composite material has high energy density, as well as excellent mechanical properties and capacitance balance characteristics; specifically, the present invention selects reasonable reagents or raw materials, and controls The conditions of each step are within the above reasonable range. First, a MXene solution is prepared by using titanium aluminum carbide and lithium fluoride / hydrochloric acid solution, and then a MoO3 nano-dispersion liquid with oxygen vacancies is prepared by using metal molybdenum and ethanol solution, and then a MoO3 / MXene blended solution is obtained; further, the present invention introduces magnesium ions into the aramid nanofiber gel, and the magnesium ions are uniformly distributed inside and / or on the surface of the aramid nanofiber gel, and the MoO3 / MXene blended solution is assembled onto the outer surface of the aramid nanofiber (ANFs) through the adsorption of the magnesium ions (i.e., positive ions), and after drying, the MoO3 / MXene is vertically distributed along the central axis of the aramid nanofiber (see Figure 1 ), the special structure of the ANFs@MoO3 / MXene composite material determines that the material has the above-mentioned excellent properties. Specifically, in the embodiment of the present invention, after the above-mentioned ANFs@MoO3 / MXene composite material is prepared, the performance test is carried out on it. The tensile strength of the ANFs@MoO3 / MXene composite material is 60~100MPa, the conductivity is 1000~2000S / cm, and the current density is 3mA / cm 3 When the volume specific capacitance is 1300~2700F / cm 3 At a current density of 5A / g, the charge and discharge cycles were 10,000 times, and the capacitance retention rate was 75~98%.
[0034] In a third aspect, the present invention provides the use of the above-mentioned aramid fiber core layer surface co-assembled array sheath structure composite material as an electrode.
[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0036] Unless otherwise specified, the raw materials used in the following examples are commercially available.
[0037] Example 1
[0038] This embodiment provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: S100, add 4.8g of lithium fluoride (LiF) to 9mol / L hydrochloric acid and stir mechanically for 10min, then slowly add 3g of titanium aluminum carbide (Ti3AlC2) precursor to the LiF / hydrochloric acid solution, stir and react at 40°C for 36h, then centrifuge and wash to neutrality, ultrasonically treat (time is 1h, power is 100w), centrifuge again for 1h to obtain a black supernatant, which is a single-layer MXene solution, and the concentration of the MXene solution is 5mg / mL; the centrifugal speed is 3500rpm; the amount of hydrochloric acid used is 45mL; S200, 0.96 g of molybdenum (Mo) powder was added to 12.5 mL of hydrogen peroxide (H2O2) solution, and the solution was rapidly stirred in an ice-water bath until the solution turned bright yellow, followed by adding 30 ml of ethanol solution; the volume ratio of ethanol to water in the ethanol solution was 2:1; the solution was hydrothermaled at 180°C for 12 hours to obtain a MoO3 nanobelt dispersion with oxygen vacancies; S300, adding the MoO3 nanobelt dispersion into the MXene solution to obtain a MoO3 / MXene blended solution; S400, dissolving the para-aramid fiber by chemical splitting to prepare a 10 mg / mL aramid nanofiber (ANFs) spinning solution; wherein the reaction temperature of the chemical splitting method is 25° C. and the reaction time is 7 days; S500, spinning the aramid nanofiber (ANFs) spinning solution through a wet spinning process, and obtaining an aramid nanofiber gel after coagulation; during the spinning process, the injection speed is set to 500 μL / min, and the coagulation bath is deionized water; S600, immersing the aramid nanofiber gel in a 1wt% magnesium chloride hexahydrate solution to obtain a Mg-containing 2+ Aramid nanofiber gel; wherein, during the dipping process, the needle specification is 15G; S700, placing the MoO3 / MXene blend solution obtained in step S300 in a culture dish, and then adding the Mg 2+ The aramid nanofiber gel is impregnated into the MoO3 / MXene blend solution for 10 minutes to obtain ANFs@MoO3 / MXene hydrogel fiber; the content of MoO3 nanobelt dispersion in the ANFs@MoO3 / MXene hydrogel fiber is 5wt%; S800, drying the ANFs@MoO3 / MXene hydrogel fiber of step S700 in a vacuum oven, the drying time is 1 hour, the drying temperature is 45°C, and the vacuum degree of the vacuum oven is 0.01 MPa, thereby preparing an ANFs@MoO3 / MXene composite material.
[0039] Example 2
[0040] This embodiment provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: S100, add 8g of lithium fluoride (LiF) to 12mol / L hydrochloric acid and stir mechanically for 10min, then slowly add 5g of titanium aluminum carbide (Ti3AlC2) precursor to the LiF / hydrochloric acid solution, stir and react at 40°C for 48h, then centrifuge and wash to neutrality, ultrasonically treat (time is 2h, power is 250W), centrifuge again for 1h to obtain a black supernatant, which is a single-layer MXene solution, and the concentration of the MXene solution is 20mg / mL; the centrifugal speed is 3500rpm; the amount of hydrochloric acid used is 75mL; S200, 1.5 g of molybdenum (Mo) powder was added to 20 mL of hydrogen peroxide (H2O2) solution, and the solution was rapidly stirred in an ice-water bath until the solution turned bright yellow, followed by adding 60 ml of ethanol solution; the volume ratio of ethanol to water in the ethanol solution was 5:1; the solution was hydrothermaled at 180°C for 12 hours to obtain a MoO3 nanobelt dispersion with oxygen vacancies; S300, adding the MoO3 nanobelt dispersion into the MXene solution to obtain a MoO3 / MXene blended solution; S400, dissolving the para-aramid fiber by chemical splitting method to prepare a 20 mg / mL aramid nanofiber (ANFs) spinning solution; wherein the reaction temperature of the chemical splitting method is 25° C. and the reaction time is 7 days; S500, spinning the aramid nanofiber (ANFs) spinning solution through a wet spinning process, and obtaining an aramid nanofiber gel after coagulation; during the spinning process, the injection speed is set to 1000 μL / min, and the coagulation bath is deionized water; S600, immersing the aramid nanofiber gel in a 1wt% magnesium chloride hexahydrate solution to obtain a Mg-containing 2+ Aramid nanofiber gel; wherein, during the dipping process, the needle specification is 15G; S700, placing the MoO3 / MXene blend solution obtained in step S300 in a culture dish, and then adding the Mg 2+The aramid nanofiber gel is impregnated into the MoO3 / MXene blend solution for 40 minutes to obtain ANFs@MoO3 / MXene hydrogel fiber; the content of MoO3 nanobelt dispersion in the ANFs@MoO3 / MXene hydrogel fiber is 30wt%; S800, drying the ANFs@MoO3 / MXene hydrogel fiber of step S700 in a vacuum oven, the drying time is 5 hours, the drying temperature is 80°C, and the vacuum degree of the vacuum oven is 0.09 MPa, thereby preparing an ANFs@MoO3 / MXene composite material.
[0041] Example 3
[0042] This embodiment provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: S100, add 6.4g of lithium fluoride (LiF) to 10mol / L hydrochloric acid and stir mechanically for 15min, then slowly add 4g of titanium aluminum carbide (Ti3AlC2) precursor to the LiF / hydrochloric acid solution, stir and react at 35°C for 40h, then centrifuge and wash until neutral, ultrasonically treat (time is 1.5h, power is 180W), centrifuge again for 1h to obtain a black supernatant, which is a single-layer MXene solution, and the concentration of the MXene solution is 15mg / mL; the centrifugal speed is 3500rpm; the amount of hydrochloric acid used is 60mL; S200, 1 g of molybdenum (Mo) powder was added to 15 mL of hydrogen peroxide (H2O2) solution, and the solution was rapidly stirred in an ice-water bath until the solution turned bright yellow, followed by adding 40 ml of ethanol solution; the volume ratio of ethanol to water in the ethanol solution was 3:1; the solution was hydrothermaled at 180°C for 12 hours to obtain a MoO3 nanobelt dispersion with oxygen vacancies; S300, adding the MoO3 nanobelt dispersion into the MXene solution to obtain a MoO3 / MXene blended solution; S400, dissolving the para-aramid fiber by chemical splitting method to prepare a 15 mg / mL aramid nanofiber (ANFs) spinning solution; wherein the reaction temperature of the chemical splitting method is 25° C. and the reaction time is 7 days; S500, spinning the aramid nanofiber (ANFs) spinning solution through a wet spinning process, and obtaining an aramid nanofiber gel after coagulation; during the spinning process, the injection speed is set to 750 μL / min, and the coagulation bath is deionized water; S600, immersing the aramid nanofiber gel in a 5wt% magnesium chloride hexahydrate solution to obtain a Mg-containing 2+Aramid nanofiber gel; wherein, during the dipping process, the needle specification is 18G; S700, placing the MoO3 / MXene blend solution obtained in step S300 in a culture dish, and then adding the Mg 2+ The aramid nanofiber gel is impregnated into the MoO3 / MXene blend solution for 30 minutes to obtain ANFs@MoO3 / MXene hydrogel fiber; the content of MoO3 nanobelt dispersion in the ANFs@MoO3 / MXene hydrogel fiber is 20wt%; S800, drying the ANFs@MoO3 / MXene hydrogel fiber of step S700 in a vacuum oven, the drying time is 2.5 hours, the drying temperature is 60°C, and the vacuum degree of the vacuum oven is 0.05 MPa, thereby preparing an ANFs@MoO3 / MXene composite material.
[0043] Example 4
[0044] This embodiment provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: S100, add 4.8g of lithium fluoride (LiF) to 9mol / L hydrochloric acid and stir mechanically for 15min, then slowly add 3g of titanium aluminum carbide (Ti3AlC2) precursor to the LiF / hydrochloric acid solution, stir and react at 40°C for 48h, then centrifuge and wash until neutral, ultrasonically treat (time is 1h, power is 100W), centrifuge again for 1h to obtain a black supernatant, which is a single-layer MXene solution, and the concentration of the MXene solution is 15mg / mL; the centrifugal speed is 3500rpm; the amount of hydrochloric acid used is 45mL; S200, 0.96 g of molybdenum (Mo) powder was added to 12.5 mL of hydrogen peroxide (H2O2) solution, and the solution was rapidly stirred in an ice-water bath until the solution turned bright yellow, followed by adding 60 ml of ethanol solution; the volume ratio of ethanol to water in the ethanol solution was 5:1; the solution was hydrothermaled at 180°C for 12 hours to obtain a MoO3 nanobelt dispersion with oxygen vacancies; S300, adding the MoO3 nanobelt dispersion into the MXene solution to obtain a MoO3 / MXene blended solution; S400, dissolving the para-aramid fiber by chemical splitting method to prepare a 15 mg / mL aramid nanofiber (ANFs) spinning solution; wherein the reaction temperature of the chemical splitting method is 25° C. and the reaction time is 7 days; S500, spinning the aramid nanofiber (ANFs) spinning solution through a wet spinning process, and obtaining an aramid nanofiber gel after coagulation; during the spinning process, the injection speed is set to 750 μL / min, and the coagulation bath is deionized water; S600, immersing the aramid nanofiber gel in a 6wt% magnesium chloride hexahydrate solution to obtain a Mg-containing 2+ Aramid nanofiber gel; wherein, during the dipping process, the needle specification is 18G; S700, placing the MoO3 / MXene blend solution obtained in step S300 in a culture dish, and then adding the Mg 2+ The aramid nanofiber gel is impregnated into the MoO3 / MXene blend solution for 20 minutes to obtain ANFs@MoO3 / MXene hydrogel fiber; the content of MoO3 nanobelt dispersion in the ANFs@MoO3 / MXene hydrogel fiber is 15wt%; S800, drying the ANFs@MoO3 / MXene hydrogel fiber of step S700 in a vacuum oven, the drying time is 5 hours, the drying temperature is 60°C, and the vacuum degree of the vacuum oven is 0.01 MPa, thereby preparing an ANFs@MoO3 / MXene composite material.
[0045] Example 5
[0046] This embodiment provides a method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, comprising: S100, add 4.8g of lithium fluoride (LiF) to 9mol / L hydrochloric acid and stir mechanically for 15min, then slowly add 3g of titanium aluminum carbide (Ti3AlC2) precursor to the LiF / hydrochloric acid solution, stir and react at 40°C for 48h, then centrifuge and wash until neutral, ultrasonically treat (time is 1h, power is 100W), centrifuge again for 1h to obtain a black supernatant, which is a single-layer MXene solution, and the concentration of the MXene solution is 15mg / mL; the centrifugal speed is 3500rpm; the amount of hydrochloric acid used is 45mL; S200, 0.96 g of molybdenum (Mo) powder was added to 12.5 mL of hydrogen peroxide (H2O2) solution, and the solution was rapidly stirred in an ice-water bath until the solution turned bright yellow, followed by adding 60 ml of ethanol solution; the volume ratio of ethanol to water in the ethanol solution was 5:1; the solution was hydrothermaled at 180°C for 12 hours to obtain a MoO3 nanobelt dispersion with oxygen vacancies; S300, adding the MoO3 nanobelt dispersion into the MXene solution to obtain a MoO3 / MXene blended solution; S400, dissolving the para-aramid fiber by chemical splitting method to prepare a 15 mg / mL aramid nanofiber (ANFs) spinning solution; wherein the reaction temperature of the chemical splitting method is 25° C. and the reaction time is 7 days; S500, spinning the aramid nanofiber (ANFs) spinning solution through a wet spinning process, and obtaining an aramid nanofiber gel after coagulation; during the spinning process, the injection speed is set to 750 μL / min, and the coagulation bath is deionized water; S600, immersing the aramid nanofiber gel in a 6wt% magnesium chloride hexahydrate solution to obtain a Mg-containing 2+ Aramid nanofiber gel; wherein, during the dipping process, the needle specification is 18G; S700, placing the MoO3 / MXene blend solution obtained in step S300 in a culture dish, and then adding the Mg 2+ The aramid nanofiber gel is impregnated into the MoO3 / MXene blend solution for 20 minutes to obtain ANFs@MoO3 / MXene hydrogel fiber; the content of MoO3 nanobelt dispersion in the ANFs@MoO3 / MXene hydrogel fiber is 5wt%; S800, drying the ANFs@MoO3 / MXene hydrogel fiber of step S700 in a vacuum oven, the drying time is 5 hours, the drying temperature is 60°C, and the vacuum degree of the vacuum oven is 0.01 MPa, thereby preparing an ANFs@MoO3 / MXene composite material.
[0047] The concentration of hydrogen peroxide (H2O2) solution in the above examples is 8wt%; the ANFs@MoO3 / MXene composite material prepared in the above examples of the present invention can be used as an electrode, and the composite material is characterized and tested for performance, please refer to Figures 1 to 3 , Figure 1 This is a partially enlarged schematic diagram of the sheath cross-sectional structure of the ANFs@MoO3 / MXene composite material prepared in Example 1 of the present invention. Figure 2 This is a schematic diagram of the planar structure of the ANFs@MoO3 / MXene composite material prepared in Example 1. Figure 3 Schematic diagram of the cross-sectional structure of the ANFs@MoO3 / MXene composite material prepared in Example 1; specifically, Figure 1 It can be seen that the sheath layer is an array structure arranged vertically along the core layer. This special structural setting can improve the electrochemical activity and electron / ion transmission efficiency of the composite material. Figure 2It can be seen that the surface of the composite material also presents a horizontal array distribution, and the molybdenum trioxide (MoO3) nanowires are evenly distributed in the MXene; Figure 3 It can be seen that the core layer of the composite material is aramid nanofibers (ANFs), which provide the composite material with excellent mechanical strength, flexibility and stability. The sheath layer is a composite layer of MoO3 and MXene, in which MoO3 improves the energy storage performance of the composite material, and MXene provides the composite material with high conductivity and excellent surface functional properties, further enhancing the electrode performance. Figure 4 It can be seen that in the ANFs@MoO3 / MXene composite material of Example 1, the XRD diffraction pattern of the core aramid nanofibers (ANFs) showed obvious peaks at 20.5°, 22.9° and 28.6°, corresponding to the characteristic diffraction peaks of its (110), (200) and (004) planes, respectively; Figure 5 It can be seen that in the ANFs@MoO3 / MXene composite material of Example 1, the XRD spectrum of the sheath MoO3 / MXene has an obvious diffraction peak at 7.5°, which is the characteristic diffraction peak of the (002) surface of MXene; and at 25.3° and 38.7°, they are the characteristic diffraction peaks of the (040) and (060) surfaces of MoO3, respectively. Figure 4 and Figure 5 It can be seen that the above Example 1 successfully prepared an ANFs@MoO3 / MXene composite material with a core layer and a sheath layer.
[0048] For further information, see Figure 6 ,from Figure 6 It can be seen that in the ANFs@MoO3 / MXene composite material prepared by the present invention, with the increase of MoO3 content, its tensile strength has been decreasing, but its elongation at break has been maintained above 10%, indicating that the composite material has good flexibility and can meet the needs of wide use in practical applications; Figure 7 It can be seen that the present invention uses a three-electrode system to test the electrochemical performance of the ANFs@MoO3 / MXene composite material. Figure 7 It can be seen that when the voltage sweep is 1mV / s (2500Fcm -3 ) showed several pairs of asymmetric redox peaks, proving that the composite material has pseudocapacitive contribution. -3 ), there is still an obvious redox peak of MoO3 under the high voltage sweep, indicating that the introduction of oxygen vacancies greatly improves the capacity of the fiber electrode and the ions have the characteristics of fast transmission in the Faraday reaction. Figure 8 It can be seen that in the ANFs@MoO3 / MXene composite material prepared by the present invention, as MoO3 It can be seen that the specific capacitance of the composite material is higher than that of the MXene electrode, which reflects the contribution of MoO3 as an electrochemically active material to the capacity of the composite material. As the content of MoO3 in the composite material gradually increases, the volume specific capacity of the composite material first increases and then decreases. The main reason is that the increase in MoO3 content will inevitably lead to an increase in the electrode radius, thereby affecting its volume and reducing the volume specific capacitance. Fig. 9 It can be seen that the ANFs@MoO3 / MXene composite material prepared by the present invention is used as an electrode, and its capacitance retention rate is 98% after 1000 charge and discharge cycles, indicating its good cycle stability. Figures 6 to 9 In the above embodiments of the present invention, the ANFs@MoO3 / MXene composite material prepared in Example 1 has higher mechanical properties and better electrochemical properties, with a tensile strength of 60MPa and a conductivity of 1000S / cm. 3 When the volume capacitance is 1400F / cm 3 At a current density of 5A / g, the charge and discharge cycles were repeated for 10,000 times, and the capacitance retention rate was 85%; the tensile strength of the ANFs@MoO3 / MXene composite material prepared in Example 2 was 80MPa, the conductivity was 1450S / cm, and the current density was 3mA / cm 3 When the volume specific capacitance is 2200F / cm 3 At a current density of 5A / g, the capacitance retention rate was 88% after 10,000 charge and discharge cycles; the tensile strength of the ANFs@MoO3 / MXene composite material prepared in Example 3 was 85MPa, the conductivity was 1500S / cm, and the capacitance retention rate was 88% after 10,000 charge and discharge cycles. 3 When the volume capacitance is 2400F / cm 3 At a current density of 5A / g, the charge and discharge cycles were repeated for 10,000 times, and the capacitance retention rate was 90%; the tensile strength of the ANFs@MoO3 / MXene composite material prepared in Example 4 was 85MPa, the conductivity was 1700S / cm, and the current density was 3mA / cm 3 When the volume specific capacitance is 2700F / cm 3 At a current density of 5A / g, the charge and discharge cycles were repeated for 10,000 times, and the capacitance retention rate was 98%; the tensile strength of the ANFs@MoO3 / MXene composite material prepared in Example 5 was 85MPa, the conductivity was 1900S / cm, and the current density was 3mA / cm 3 When the volume capacitance is 2400F / cm 3, at a current density of 5A / g, the capacitance retention rate is 95% after 10,000 charge and discharge cycles. The above technical solution of the present invention solves the technical problems that the energy density of the existing fiber-assembled fiber-shaped supercapacitor is low and the balance between mechanical properties and capacitance cannot be achieved.
[0049] In the description of the above embodiments, specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples.
[0050] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure, characterized in that: include: Titanium aluminum carbide is added to a lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained; Add metal molybdenum and ethanol solution to hydrogen peroxide solution and perform hydrothermal treatment for 6 to 12 hours to obtain MoO3 nano-dispersion with oxygen vacancies; wherein the temperature of the hydrothermal treatment is 140 to 180°C, and the concentration of the ethanol solution is 20 to 50 Vol%; Obtaining a MoO3 / MXene blended solution according to the MXene solution and the MoO3 nanodispersion; The aramid nanofiber gel containing magnesium ions is impregnated into the MoO3 / MXene blend solution, and after drying, an ANFs@MoO3 / MXene composite material is obtained.
2. The method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure according to claim 1, characterized in that: In the lithium fluoride / hydrochloric acid solution, the concentration of hydrochloric acid is 9-12 mol / L; the volume of hydrochloric acid required for every 4-8 grams of lithium fluoride is 30-120 mL; and / or, The mass ratio of the titanium aluminum carbide to the lithium fluoride is 1:(1.6-2).
3. The method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure according to claim 2, characterized in that: The titanium aluminum carbide is added to the lithium fluoride / hydrochloric acid solution, and after stirring and centrifugation, a MXene solution is obtained, comprising: Adding the titanium aluminum carbide to the lithium fluoride / hydrochloric acid solution, and stirring for 20 to 50 hours at a temperature of 25 to 50° C. to obtain a first solution; the stirring rate is 100 to 150 rpm; The first solution is centrifuged, washed to neutrality, and subjected to ultrasonic treatment for 1 to 2 hours to obtain a second solution; the centrifugal speed is 3000 to 4000 rpm, and the ultrasonic treatment power is 100 to 250 W; After the second solution is centrifuged again, a supernatant is obtained; the supernatant is the MXene solution; wherein the re-centrifugation rate is 1000~4000rpm, and the centrifugation time is 0.5~2 hours.
4. The method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure according to claim 3, characterized in that: In the process of adding the metal platinum and the ethanol solution to the hydrogen peroxide solution, the mass of the metal platinum required for each 12-20 mL of the hydrogen peroxide solution is 0.5-2 grams; and / or, The volume ratio of the ethanol solution to the hydrogen peroxide solution is 1:(0.5~1).
5. The method for preparing the composite material of aramid fiber core layer surface co-assembled array sheath structure according to claim 4, characterized in that: In the MoO3 / MXene blended solution, the volume ratio of the MXene solution to the MoO3 nano-dispersion solution is 1:(0.05-0.15).
6. The method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure according to claim 5, characterized in that: In the process of impregnating the aramid nanofiber gel containing magnesium ions into the MoO3 / MXene blended solution, the mass ratio of the aramid nanofiber gel containing magnesium ions to the MoO3 / MXene blended solution is 1:(100~150).
7. The method for preparing the composite material of the aramid fiber core layer surface co-assembled array sheath structure according to claim 6, characterized in that: The magnesium ion content in the aramid nanofiber gel containing magnesium ions is 5-10wt%; and / or, The method for obtaining the aramid nanofiber gel containing magnesium ions comprises: The para-aramid fiber is dissolved to prepare a 10-20 mg / mL aramid nanofiber spinning solution; The aramid nanofiber spinning solution is subjected to spinning treatment to obtain an aramid nanofiber gel after coagulation; the injection speed of the spinning treatment is 500-1000 μL / min, and the coagulation bath is deionized water; The aramid nanofiber gel is immersed in a 1-10 wt % magnesium chloride hexahydrate solution and mixed evenly to obtain the aramid nanofiber gel containing magnesium ions.
8. The method for preparing the composite material of aramid fiber core layer surface co-assembled array sheath structure according to claim 7, characterized in that: The drying process is carried out in a vacuum environment; The vacuum degree of the vacuum environment is 0.01-0.09 MPa, the drying temperature is 35-80° C., and the drying time is 0.5-6 hours.
9. A composite material of aramid fiber core layer surface co-assembled array sheath structure, characterized in that: Prepared according to the method for preparing a composite material of an aramid fiber core layer surface co-assembled array sheath structure according to any one of claims 1 to 8; Among them, the core layer of the composite material of the co-assembled array sheath structure on the surface of the aramid fiber core layer is aramid nanofiber, and the co-assembled array sheath structure is MoO3 / MXene; the co-assembled array sheath structure surrounds the aramid nanofiber and is vertically distributed along the central axis of the aramid nanofiber.
10. Use of the aramid fiber core surface co-assembled array sheath structure composite material according to claim 9 as an electrode.
Citation Information
Patent Citations
Preparation methods of molybdenum trioxide and hydrogen-doped molybdenum trioxide as supercapacitor materials
CN106298264A
Preparation method of high-performance supercapacitor electrode
CN107742588A
Aramid nanofiber / MXene composite conductive aerogel and preparation method thereof
CN111040238A
Preparation method of aramid nano-based composite conductive fiber
CN113235184A
Preparation and application of PANI / MoO3-x shell-core composite electrode material with electrochromic function
CN113314354A